Students' Speaking Anxiety during Online Learning: Causal Factors and Strategies to Overcome Them (A Narrative Inquiry Study at Islamic Senior Secondary School (MAN) Insan Cendekia Gowa) - Muhammad Alauddin Nur; Sultan Baa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Anxiety has been considered as one of the obstacles in learning English and a common issue in the EFL teaching and learning. In speaking, it also debilitates the opportunity of English Foreign Language (EFL) students to speak English. Several studies have been conducted to discover the causes and straegies to overcome them in traditional classroom. To date, not many studies have focused on students’ anxiety in online learning. Therefore, this study was designed to reveal the causal factors of the students’ speaking anxiety and strategies to overcome them during online learning at Islamic senior secondary school setting. The study employed narrative inquiry approach and used interview as the main instrument of data collection. Four students of Islamic Senior Secondary School (MAN) Insan Cendekia Gowa whom selected to be the participants of the study using purposive sampling technique. The result of this study establishes two main findings. Firstly, the causal factors of students' speaking anxiety during online learning were divided into internal and external factors. The internal factors consisted  of lack of confidence, shyness, fear of making mistake, and feeling insecure. The external factors consisted of lack of preparation, limited vocabulary, friends or classmates, embarrassment, teachers’ teaching style. The study found that the external factors are indicated as the most dominant causes of students' speaking anxiety. Furthermore, the study highlights several strategies used by the students to overcome their speaking anxiety, namely: good preparation (lecture note), peer seeking, keeping silent or calm, practice speaking at home, turning the camera off, using ‘google translator’, and limiting speaking duration.